A survey of malaria and some arboviral infections among suspected febrile patients visiting a health centre in Simawa, Ogun State, Nigeria - Adenola F. Ayorinde; Ayorinde M. Oyeyiga; Nwakaego O. Nosegbe; Onikepe A. Folarin (Elsevier, 2016)
Summary: Most febrile patients are often misdiagnosed with malaria due to similar symptoms, such as fever shared by malaria and certain arboviral infections. This study surveyed the incidence of malaria, chikungunya and dengue infections among a number of suspected febrile patients visiting Simawa Health Centre, Ogun State, Nigeria.Venous blood samples were obtained from 60 febrile patients (age 3-70 years) visiting the centre between April and May 2014. The rapid diagnostic test (RDT) was used to detect the presence of chikungunya (CHK) antibodies (IgM), dengue (DEN) virus and antibodies (NS1, IgM and IgG) and malaria parasites (Plasmodium falciparum and Plasmodium vivax). Malarial confirmatory tests were by microscopy and nested polymerase chain reaction (PCR) using the polymorphic region of Glutamate-Rich Protein (GLURP) gene. The complexity of P. falciparum infection in the community also determined by the use of nested PCR. These three mosquito-borne infections were observed in 63% (38) of the patients. The prevalence of CHK, DEN and malarial infections singularly were 11%, 0% and 63%, respectively, whereas malaria with either CHK or DEN infections were 24% (9) and 3% (1), respectively. No subjects were positive for CHK and DEN co-infection. Malarial microscopic confirmation was in 94% (32) of the malaria RDT-positive samples, 50% (17) were successfully analysed by nested PCR and the mean multiplicity of infection was 1.6 (1-3 clones). One patient sample harboured both P. falciparum and P. vivax. The study reports the presence of some arboviral infections having similar symptoms with malaria at Simawa, Ogun State. The proper diagnosis of infectious diseases is important for controlling them. Keywords: Malaria, Chikungunya, Dengue, Plasmodium falciparum, Plasmodium vivax, Febrile